Oncolytic herpes viruses, chemotherapeutics, and other cancer drugs - Braidwood, Lynne (Oncolytic Virother, 2013)
Oncolytic viruses are emerging as a potential new way of treating cancers. They are selectively replication-competent viruses that propagate only in actively dividing tumor cells but not in normal cells and, as a result, destroy the tumor cells by consequence of lytic infection. At least six different oncolytic herpes simplex viruses (oHSVs) have undergone clinical trials worldwide to date, and they have demonstrated an excellent safety profile and intimations of efficacy. The first pivotal Phase III trial with an oHSV, talimogene laherparepvec (T-Vec [OncoVex(GM-CSF)]), is almost complete, with extremely positive early results reported. Intuitively, therapeutically beneficial interactions between oHSV and chemotherapeutic and targeted therapeutic drugs would be limited as the virus requires actively dividing cells for maximum replication efficiency and most anticancer agents are cytotoxic or cytostatic. However, combinations of such agents display a range of responses, with antagonistic, additive, or, perhaps most surprisingly, synergistic enhancement of antitumor activity. When synergistic interactions in cancer cell killing are observed, chemotherapy dose reductions that achieve the same overall efficacy may be possible, resulting in a valuable reduction of adverse side effects. Therefore, the combination of an oHSV with “standard-of-care” drugs makes a logical and reasonable approach to improved therapy, and the addition of a targeted oncolytic therapy with “standard-of-care” drugs merits further investigation, both preclinically and in the clinic. Numerous publications report such studies of oncolytic HSV in combination with other drugs, and we review their findings here. Viral interactions with cellular hosts are complex and frequently involve intracellular signaling networks, thus creating diverse opportunities for synergistic or additive combinations with many anticancer drugs. We discuss potential mechanisms that may lead to synergistic interactions.